Pengaturan Jenis Pekerjaan dan Jangka Waktu Pekerja/Buruh Alih Daya Pasca Berlakunya Undang-Undang Nomor 6 Tahun 2023 - Hana Gracia Berliana; Purwono Sungkowo Raharjo; Rosita Candrakirana (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The Employment Law defines employment relationships and types of work agreements in Indonesia, including fixed-term work agreements (PKWT) and indefinite-term work agreements (PKWTT). Apart from that, the discussion also includes outsourcing and the impact of the Job Creation Law, which is viewed differently by various parties, with concerns that the law benefits employers more than workers/laborers. This research uses doctrinal/normative research methods. The aim of this research is to determine the regulation of the type of work and term of outsourced workers/laborers after the enactment of Law Number 6 of 2023. Based on the research and discussions carried out, it is concluded that the Job Creation Law is still unable to provide protection and facilitate rights. - maximum outsourcing worker/labor rights. First, regarding the type of work, the enactment of the Job Creation Law officially expands the scope of types of work that can be done by outsourced workers/laborers which were initially only limited to supporting non-core business, but with the enactment of the Job Creation Law, it was expanded to core business work. . Second, currently outsourced workers/laborers can be employed using a Certain Time Work Agreement (PKWT) or an Indefinite Time Work Agreement (PKWTT) system. With the enactment of the Job Creation Law, the maximum term limit for PKWT workers, which was previously set at three years in the Manpower Law, has now been extended to five years.